AB1059 CRMO in adults: Does it really exist? difficult differential diagnosis with suprising results. (23rd January 2014) - Haas, F.; Zeh, G.; Schmalzing, M.; Henes, J.; Kanz, L.; Horger, M.; Kurth, R.R.; Koetter, I.
Abstract : Background: CRMO is a rare condition (about 1:1.000.000) with clinical signs of osteomyelitis but is without detection of any bacterial or fungal agents. Due to its inflammatory character, the missing of any known pathogen and its relapsing remitting course, CRMO is classified as an auto (?) inflammatory disease. CRMO must be seen as an exclusion diagnosis. In the past, CRMO was considered to be a disease exclusively limited to childhood. More recently, cases in adults have been described, however, there may be an increased risk of misdiagnosis Results: Cases: Female patient, 53 years. Pain in the region of Os ileum und elevated inflammation signs in laboratory findings. Plain radiographic findings showed osteosclerotic lesions, the MRI osteolytic lesions. Two bone biopsies of Os ileum were fitting to CRMO. Uprising B-symptoms over 5 month and an inguinal lymphadenopathy lead after another bone biopsy of Os ileum to the diagnosis of a diffuse large B-cell lymphoma. Male patient, 48 years. Lower back pain and elevated inflammation signs in laboratory findings. CT-scan showed signs of Paget's disease (sclerotic lesion). The biopsy was consistent with CRMO. Prolonged B-symptoms ad lymphadenoathy over 3 month finally revealed the nodular sclerosing Hodgkin's lymphoma. Male patient, 37 years. Clinical diffuse sceletal pain in the spinal column and B-symptoms for 8 month months. CT scan with multiple osteolytic lesions in the spinal column. Two biopsies in different localisations showed CRMO. During immunosuppressive treatment, which was due to inefficacy intensified stepwise - finally under etanercept - unmasked the underlying Hodgkin's lymphoma. Female patient, 39 years. Diagnosis of CRMO due to bone biopsy proximal tibia witch showed osteomyelitis. Under MTX and bisphosphonates there was initially a good response over more than two years. Then progress with pain and local inflammation. In the bone biopsy of the proximal tibia a follicular Non-Hodgkin-Lymphoma was proven. Interestingly, even after knowledge of the final diagnosis and critical reevaluation of the biopsies histopathologically, still these showed CRMO (lymphoctic and neutrophilic, mnocytic infiltrates without any evidence of monoclonality/lymphoma). Conclusions: These four cases show that despite of typical clinical symptoms, imaging and histopathological findings, the diagnosis of CRMO in adults should always be questioned. This is of utmost importance not only before starting immunosuppressive treatment, but also in case of insufficient efficacy of therapy. The major differential diagnosis of CRMO in adulthood is intraosseous lymphoma, which probably as paraneoplastic phenomenon histopathologically may mimick CRMO. The signs of this autoinflammatory disease are local pain, systemic inflammatory sings (B-symptoms), laboratory findings of inflammation with elevated C-reactive protein level, erythrocyte sedimentation rate, peripheral leukocytes and ferritin level. Furthermore the MRI that reveals the inflammation and/or lesions, plain radiographic findings with osteolytic, sclerotic, or a mixed lytic-sclerotic lesion. All these are also typical of lymphoma, not only of CRMO and unspecific. Disclosure of Interest: None Declared.